Shifting Perspectives on the European Public Prosecutor's Office (T.M.C. Asser Press, 2018)
This book provides answers to the following questions. Is there a bright future ahead for a European Public Prosecutor's Office? If so, is the regulation establishing the office sufficiently clear and balanced to attain that goal? Moreover, will the office be able to effectively fight fraud now damaging the EU's budget and will it respect the fundamental rights of the parties involved? Included are issues ranging from EU substantive and procedural criminal law, combatting EU fraud, the distribution of competences in European law enforcement, EU fundamental rights, to forum choice. The book's aim is to inform academics, policy-makers and criminal law practitioners about key issues surrounding the attribution of prosecutorial powers to an entirely remodelled European Union body. In doing so, it sheds light on this body, as fundamentally changed by the Council, which will undoubtedly have a greater impact on the European criminal justice system than the European Arrest Warrant ever did. Dr. Willem Geelhoed is Assistant Professor in criminal law and criminal procedure at the University of Groningen, The Netherlands, and Drs. Leendert H. Erkelens and Prof. Mr. Arjen W.H. Meij are both Visiting Research Fellow at the T.M.C. Asser Instituut in The Hague in The Netherlands, while the latter is also Honorary Professor at the University of Luxembourg.